An upconversion nanoprobe operating in the first biological window1. Issue 17 (7th May 2015) - Ju, Qiang; Chen, Xian; Ai, Fujin; Peng, Dengfeng; Lin, Xudong; Kong, Wei; Shi, Peng; Zhu, Guangyu; Wang, Feng
<x xml:space="preserve">Abstract</x> A core–shell–shell upconversion nanoprobe is developed to generate 660 nm emission by 808 nm excitation.